Concurrent Repair of Inguinal Hernias with Mesh Application During Transperitoneal Robotic-assisted Radical Prostatectomy: Is it Safe? - Atmaca, Ali Fuat; Hamidi, Nurullah; Canda, Abdullah Erdem; Keske, Murat; Ardicoglu, Arslan (Urology Journal, 2018)
Purpose: To assessment the safety of concurrent repair of inguinal hernia (IH) with mesh application during transperitoneal robotic-assisted radical prostatectomy(RARP). Materials and Methods: Data of 20 patients (totally 25 procedures) who performed concurrent IH repair with mesh application during RARP were retrospectively enrolled in this study. Preoperative patient characteristics, intra and postoperative parameters (pathological Gleason grade, prostate volume at surgical specimen, operative time, herniorrhaphy time, estimated blood loss, complications, time of hospitalization, catheterization, and drainage) were evaluated. Standard PSA control and postoperative complications of mesh application such as hernia recurrence, mesh infection, seroma formation and groin pain were evaluated at every follow-up visits (every three in the first year, then every 6 months in years 2 to 5 and annually thereafter. Result: The mean age was 66 ± 8 years in our population. Fifteen (60 %) patients had a unilateral hernia and 5 (40%) patients had bilateral hernias. The mean operative time was 139 ± 21minutes and estimated mean blood loss was 108 ± 76 mL. The mean duration of IH repair in patients which was 27 ± 5 (range: 17- 40) minutes. The mean time of drainage, hospitalization, and catheterization were 2.5 ± 0.8 days (range: 2-6), 4 ± 0.9 days (range: 2-7) and 8.2 ± 1.9 days (range: 7-14), respectively. We did not observe any intra-operative complication due to RARP or IH repair. Wound evisceration at camera port site developed in only a patient on postoperative day 20. Our median follow-up time was 13 months and we did not observe mesh infection or hernia recurrence during follow-up. Conclusion: Concurrent IH repair with RARP procedure seem to be easy to perform, effective and safe procedure.